PHENOMENOLOGICAL STUDY OF MOTHER'S EXPERIENCE IN PROVIDING EARLY SEXUAL EDUCATION TO SCHOOL CHILDREN IN NGAMBAR BAMBE VILLAGE - Eko Budi Santoso,; Choi Datul Rohma Wati, (International Journal of Social Science, 2024)
Sexual education provided to children is not just about teaching anatomy, reproduction, or methods of intercourse; rather, it aims to provide understanding tailored to their age about the functions of sexual organs (Noeratih, 2015 Nurhayati & Rasyid, 2019). This research employed a qualitative research method with a phenomenological approach, utilizing total sampling technique and involving 6 informants. Data collection techniques included in-depth interviews and documentation. Through in-depth interviews with the 6 informants, 6 themes were identified: 1) mothers' knowledge about sexual education, 2) mothers' experiences in providing sexual education to their children, 3) methods mothers use to provide sexual education to their children, 4) the first things mothers discuss when providing sexual education to their children, 5) how mothers explain sexual education to their children, and 6) challenges mothers face in providing sexual education. This study explores mothers' knowledge and experiences regarding the provision of sexual education. Based on the research findings and thematic analysis